Fund Management in Politeknik Kesehatan Kemenkes Bandung - Subandi, Subandi (International Journal Labs, 2023)
This study is centered on the analysis of the financial practices implemented at the Politeknik Kesehatan Kemenkes Bandung. Furthermore, it delves into the realms of financial management and explores the resources related to student financing within the institution. Employing a qualitative-descriptive research methodology, it seeks to provide a comprehensive portrayal of the circumstances surrounding education financing within this academic establishment. It's important to note that this study does not aim to establish causal relationships or quantify effects. Instead, it focuses on offering a detailed and insightful overview of management practices and their alignment with regulations. The data for this research was meticulously gathered through a variety of methods, including observation instruments, interviews with key stakeholders, and an in-depth review of relevant literature. This multi-faceted approach ensures a well-rounded understanding of the subject matter. The findings of this study shed light on the Politeknik Kesehatan Kemenkes Bandung's management of education financing. Notably, these findings indicate a strong degree of compliance with the applicable regulations. This suggests that the institution is conscientious in its financial management practices, ensuring that it meets the legal and regulatory standards in place. This study underscores that the Politeknik Kesehatan Kemenkes Bandung's management of education financing is aligned with the stipulations set forth in relevant laws and regulations. Furthermore, it operates with a commitment to the core principles of transparency, objectivity, and accountability, which are vital in ensuring that educational resources are managed in a manner that serves the best interests of both the institution and its students.